ENGLISH LEARNING DIFFICULTIES AT SMP NEGERI 23 TAKENGON DURING THE PANDEMIC - Yunie Amalia RakhmytaMRs. (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2022)
This study described the difficulties faced by students in learning English during the pandemic at SMP Negeri 23 Takengon. The researchers applied a qualitative study with a phenomenological approach in this current research. Data were collected through several techniques comprising observation, interviews, and documentation. The study used three steps from Miles and Huberman's theory to analyze the data, including data reduction, data display, and conclusions. The results showed that the students face five difficulties in learning English amidst the pandemic comprising learning disorders, learning disabilities, learning dysfunctions, underachievers, and slow learners. Among those five, slow learners become the most dominant difficulty, while learning disorder is the least problematic aspect for the students. Several issues that are likely to cause difficulties are a continuous practice of multiple-choice questions without being given a context, avoiding class, lack of interest in learning English, weak ability to learn fast, and reduced learning hours.